Observer design for systems with unknown inputs - Hui, Stefen; Żak, Stanisław H. (Zielona Góra: Uniwersytet Zielonogórski)
Design procedures are proposed for two different classes of observers for systems with unknown inputs. In the first approach, the state of the observed system is decomposed into known and unknown components. The unknown component is a projection, not necessarily orthogonal, of the whole state along the subspace in which the available state component resides. Then, a dynamical system to estimate the unknown component is constructed. Combining the output of the dynamical system, which estimates the unknown state component, with the available state information results in an observer that estimates the whole state.
Keywords: state observation; unknown input observer (UIO); uncertain systems; projection operators; second method of Lyapunov